Academic Administration Guidelines for Develop 21st Century Learning Skills of Students Under the Sukhothai Primary Educational Area Office 2 - Oungern, Rattiyakorn; Thammasit , Phimphaka; Panyasai , Vajee (Journal of Modern Learning Development, 2022)
The purpose of this research was to study the current conditions and the needs and requirements. Academic administration to develop learning skills in the 21st century of students under the Sukhothai Primary Educational Service Area Office 2. The samples used in the research were: 91 school administrators and 91 academic heads totaling 182 participants by using the table of Krejcie & Morgan: and 8 specialists. The research instruments for data collection were a questionnaire and a group discussion. The analytical devices included frequency, percentage, mean, standard deviation and content analysis. The results were as follows. 1) the current condition and the need for academic administration to develop 21st century learning skills of students under the Sukhothai Primary Educational Service Area Office 2 overall were at a high level. The most demanding aspect is in the aspect of monitoring and evaluation, and 2) A guideline for academic administration to develop learning skills in the 21st century of students under the Sukhothai Primary Educational Service Area Office 2 is that schools use a variety of measurement and evaluation tools to develop students' learning skills. knowledge in the 21st century. Therefore, measurements and assessments should be measured and evaluated in a variety of ways and assessed from the real situation of learners. Classroom teaching is integrated to provide learners with 21st century skills.